Results from Bottom Trawl Survey on Flemish Cap of July 2002 - Saborido-Rey, Fran; Vázquez Rodríguez, Antonio (Northwest Atlantic Fisheries Organization, 2003)
41 páginas, 7 figuras, 32 tablas. A stratified random bottom trawl survey on Flemish Cap was carried out on July 2002 up to a depth of 730 m. Survey results are presented and compared with those of previous surveys in the series since 1988. Abundance at age indices was presented for cod, American plaice, redfish and Greenland halibut. Peer reviewed